Refugees from Nazism to Britain in Trade, Industry, and Engineering - Brinson, Charmian; Nyburg, Anna (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
From an unlikely Technical College in internment, run by the dubious character Ludwig Warschauer or the unusual female electrical engineer Ira Rischowski, to the unprecedented and creative initiative that was the trading estates where many refugees set up their businesses, this book is full of surprises. You may be intrigued to learn how much the refugees contributed to the British War Effort: from Ludwig Löwy who created new aircraft for the RAF, to Londex, a little known engineering company which made lighting equipment for buoys and submarines, and many others, these case studies reveal how the refugees helped Britain win the war. Contributors are: Tony Morgan, Scott Cairns, Tiffany Beebe, Andrea Hammel, Anna Nyburg, Simon Willey, Cathryn Enis, Simon Parkin, Felicitas Starr-Egger, Jonathan Aylen C, Charmian Brinson, Rob David, Stephen Richardson, Nicholas Russell, Esther Saraga, and Miriam David.